The level of dental fear and anxiety is higher in children with both severe Molar-Incisor Hypomineralisation and active dental caries lesions compared to children without these conditions - Rodríguez, A.; Laverde, M.; Rojas-Gualdrón, D. F.; Cárdenas, J. M.; Mejía, J. D.; de Farias, A. L.; Santos-Pinto, L. [UNESP]; Restrepo, M. (Springer Nature, 2024)
Purpose: To assess levels of dental fear and anxiety (DFA) in children with and without Molar-Incisor Hypomineralisation (MIH) and dental caries lesions. Methods: In this cross-sectional observational study, 159 children between 8 and 12 years of age were included. For the evaluation of DFA, children responded to the validated version of the Children’s Fear Survey Schedule-Dental Subscale. MIH was assessed using the MIH Index. To evaluate the activity of dental caries lesions and dental caries experience, the Nyvad criterion and the dmft/DMFT index were used, respectively. Dental hypersensitivity was evaluated using air stimulation and a Visual Analogue Scale. The association between MIH and dental caries with DFA was assessed using the generalised linear model with Poisson family, identity link function and robust variance estimation. The significance level was set at 5%. Results: The mean DFA score was 28.3 (SD = 13.4) with scores ranging from 15 to 64. Amongst children presenting both MIH and dental caries, the perception of DFA was notably higher compared to those with either MIH or dental caries alone. The activity of caries lesion in patients with MIH also influenced DFA levels (diff: 18.6; 95% CI: 12.0–25.2; p < 0.001). Dental caries experience in the primary dentition also demonstrated statistical significance concerning DFA (95% CI: 0.8–13.3; p value = 0.027). Conclusion: Children with MIH exhibit higher levels of DFA than children without MIH. The experience of dental caries and the activity of caries lesions significantly influence the perception of DFA in children with MIH.
Keywords: Behaviour; Child; Dental anxiety; Developmental defects of enamel